Algebra and Trigonometry 10th Edition

Published by Cengage Learning
ISBN 10: 9781337271172
ISBN 13: 978-1-33727-117-2

Chapter 5 - 5.1 - Exponential Functions and Their Graphs - 5.1 Exercises - Page 369: 48


$x_1=3$ and $x_2=2$

Work Step by Step

$e^{x^2+6}=e^{5x}$ Applying the One-to-One Property: $x^2+6=5x$ $x^2-5x+6=0$ ($a=1,~b=-5,~c=6$) $x=\frac{-(-5)±\sqrt {(-5)^2-4(1)(6)}}{2(1)}$ $x=\frac{5±\sqrt {1}}{2}=\frac{5±1}{2}$ $x_1=\frac{6}{2}=3$ and $x_2=\frac{4}{2}=2$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.